Business Analogies at Church: A Hermeneutical Study into the Use of Analogy for Missional Church Leadership - Robinson, Ian (Ecclesial Futures, 2021)
A significant weakness in leadership studies is the free use of cross-sector analogies without a hermeneutical standard. Churches need new approaches from other sectors but may respond with little critical method, either too freely or too narrowly. Many reject any need to learn from outside the Church. The practical goal of this paper is to provide a way to learn without risking the Church’s own character. This is the work of analogy. While referencing the theological and missiological histories of this method, the argument is based on analysis of the hermeneutical principles in Jesus’ parables compared with the epistemology of analogy in education and interdisciplinary studies. An analogical hermeneutic is then applied to two business examples. The analogical hermeneutical spectrum, I propose, can nourish the wisdom of church leaders and enhance a church’s collective efficacy. In conclusion, further research avenues are suggested.